The Effect of 2016 Chinese second-child policy and different maternal age on pregnancy outcomes in Hebei Province, China - Mei-Ling Tian; Guo-Juan Ma; Li-Yan Du; Ying Jin; Cui Zhang; Yuan-Ge Xiao; Zeng-jun Tang (BMC, 2023)
Abstract Objective To explore the effect of the 2016 Chinese second child policy and different maternal ages on adverse perinatal outcomes. Methods Clinical data were collected from 22 monitoring hospitals in Hebei Province from January 1, 2013, to December 31, 2021. A total of 413,892 parturient were divided into 3 groups based on delivery age: 20-34, 35-39, and 40-55 years old. The clinical data were analyzed to explore the relationship among the 2016 Chinese second-child policy, maternal age, and various pregnancy risks. Results Pregnancy complications showed an upward trend from 2013 to 2021.The top 10 incidences of pregnancy complications in Hebei Province were anemia, small for gestational age (SGA), large for gestational age (LGA), macrosomia, gestational diabetes mellitus (GDM), premature delivery, preeclampsia (PE), postpartum hemorrhage (PPH), placenta previa, and placental abruption. The two-child policy was implemented in 2016. The incidence of pregnancy complications, anemia, GDM, PE, placental abruption, cesarean delivery, premature delivery, SGA, LGA, macrosomia in 2016-2021 was significantly higher than that in 2013-2015 (P<0.05), and the proportion of women of advanced maternal age (AMA, ≥ 35 years old) increased from 2013 to 2021. Advanced maternal age was a risk factor for most assessed adverse pregnancy outcomes, including GDM, PE, placenta previa, placenta abruption, cesarean delivery, PPH, premature delivery, SGA, LGA and macrosomia. Conclusion After the adjustment of the "second-child" policy, the incidence of pregnancy complications increased. Moreover, the risk of adverse pregnancy outcomes in AMA has increased. Early prevention and intervention should be implemented to cope with the occurrence of adverse perinatal outcomes.